Nilai-nilai dan Parameter Demokrasi dalam Kehidupan Masyarakat Bali - I Wayan Gede Suacana (Jurnal Kajian Bali (Journal of Bali Studies), 2015)
AbstractBalinese culture has a lot of potential values of democracy which up till now still become the basis in the society’s life. To explore this potentiality, this study is trying to explain how the manifestation of the normative democratic values and the empirical democracy are implemented in society of Bali. This writing is based on the research which used qualitative method that covered the collection of primary and secondary data, theories of analyzing data, analysis and interpretation of already selected data. Writing and constructing the whole result of this research were also done in this study. Based on the result of this research, it was found that the manifestation of the normative democratic values show that there were respects for the individual rights, obedience political fatsoen, the spirit of cooperation, rotation of the autority and periodical succesion, equality and respect for citizen ’rights, tolerance in dessent, transparency and accountabilty of the authority holders, and participation in public policy. Meanwhile, the empirical manifestation of the democracy which is reflected in many aspects of Balinese lifegreatly affects how the describe the concept of democracy as the basis of the strength and independence of the transition of the democracy happening nowdays. The application of the values and the parameter of the democracy also influence the form and the characteristic of the relation between Balinese society and the government as part of the institution.